Effectivity of Shark Cartilage (Carcharhinus sorrah) Ointment Extract on Growth of Lizard (Mabouya multifasciata kuhl) Regenerated Tail - Rakhmiyati Rakhmiyati (Universitas Airlangga, 2023)
Shark (Carcharhinus sorrah) is a fish whose entire endoskeleton is composed of cartilage. Fish cartilage is widely used for treatment because shark cartilage (SC) contains glucosamine (GS) and chondroitin sulfate (CS) compounds. This study aims to determine the benefits of glucosamine and chondroitin sulfate derived from SC extract on lizard tail regeneration. The study was initiated by testing the characteristics of the SC extract ointment which included tests of spreadability, pH, viscosity and adhesion of the ointment. The effectiveness test of SC extract ointment was done using 36 lizards that were autotomized and divided into 4 treatment groups. The treatment in the form of SC extract ointment with concentrations of 0% (control), 5%, 10%, and 15% was applied to the autotomized tail every morning and evening. The lizards were then kept for 7; 18; and 35 days. The test data for the physicochemical character of the SC extract ointment were analyzed using one-way ANOVA with a significance level of 5% (p<0.05) and the lizard regeneration tail length data were analyzed using a two-way ANOVA with a significance level of 5%. (p<0.05). The result of the research showed that there was a significant difference in the physicochemical character of the spread of SC extract ointment, meanwhile the other physicochemical characters showed no significant difference. The SC extract ointment used in this study was not effective in the growth of lizard regenerate tails.